Formulation and evaluation of irbesartan fast dissolving tablets - Ramu, Anne; Vidyadhara, Suyadevara; Devanna1, Nayakanti; Naidu, Uttlapalli Thirumala; Kalyani, Pavuluri Lakshmi (Asian Journal of Pharmaceutics (AJP), 2014)
Solid dispersions of irbesartan with poly ethylene glycol (PEGâ€6000) were prepared and further compressed as tablets by using superdisintegrants such as croscarmellose sodium, crospovidone, sodium starch glycolate (SSG). The solid dispersions of irbesartan with PEGâ€6000 at different ratios were prepared by physical mixing, solvent evaporation and kneading methods. The rapid release of poorly soluble irbesartan from solid dispersions was influenced by the proportion of polymer and the method employed for its preparation. Among the three methods employed kneading method was found to be suitable for improving the dissolution rate of irbesartan. The release was found to follow the first order kinetics.Solid dispersions prepared by the kneading method were further formulated into tablets with superdisintegrants such as croscarmellose sodium, crospovidone, SSG. All the tablet preparations containing superdisintegrants were formed to release the drug in the order SSG > cross carmellose sodium > cross povidone. The dissolution rate of such tablet formulations were found to release the drug at a faster rate than the tablets prepared with plain drug.